2008
DOI: 10.1209/0295-5075/83/17002
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity and phase diagram in iron-based arsenic-oxides ReFeAsO 1−δ (Re = rare-earth metal) without fluorine doping

Abstract: Here we report a new class of superconductors prepared by high pressure synthesis in the quaternary family ReFeAsO 1-d (Re = Sm, Nd, Pr, Ce, La) without fluorine doping. The onset superconducting critical temperature (T c ) in these compounds increases with the reduction of Re atom size, and the highest T c obtained so far is 55 K in SmFeAsO 1-d . For the NdFeAsO 1-d compound with different oxygen concentration a dome-shaped phase diagram was found.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
412
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 689 publications
(423 citation statements)
references
References 16 publications
9
412
1
1
Order By: Relevance
“…The single crystalline nature of the samples was checked by Laue X-ray diffraction [38]. Our crystals, whose T c (≈ 35 K) is lower than the optimum T c ≈ 51 K of PrFeAsO 1−y [39], are in the underdoped regime (y ∼ 0.1) [40], which is close to the spin-density-wave order [41]. The sample homogeneity was checked by magneto-optical (MO) imaging [37].…”
Section: Experimental a Single Crystalsmentioning
confidence: 98%
“…The single crystalline nature of the samples was checked by Laue X-ray diffraction [38]. Our crystals, whose T c (≈ 35 K) is lower than the optimum T c ≈ 51 K of PrFeAsO 1−y [39], are in the underdoped regime (y ∼ 0.1) [40], which is close to the spin-density-wave order [41]. The sample homogeneity was checked by magneto-optical (MO) imaging [37].…”
Section: Experimental a Single Crystalsmentioning
confidence: 98%
“…[9] Superconducting 1111-materials have also been produced by the introduction of O-vacancies. [10] Here we describe the results of isoelectronic substitution of Ru for Fe in PrFeAsO 1111-type materials which fully suppresses the SDW transition resulting in a metallic state that does not exhibit superconductivity above 2 K.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Superconductivity has been observed with transition temperatures (T C ) as high as 52 K in PrFeAsO 1−x F x and 51 K in PrFeAsO 1−y . [14,10] It has been shown that the superconductivity in these systems is quite robust against disorder, even disorder in the Fe plane. [6,15] It is possible that disorder alone, without charge carrier doping, may be enough to suppress the SDW so that superconductivity could emerge.…”
Section: Introductionmentioning
confidence: 99%
“…An example is the maximum T c of approximately 56 K achieved by the substitution of rare-earth ions in the 1111 system. 29 It is thus somewhat surprising that substitution of K by Rb, Cs, or Tl in the new superconductors leaves T c essentially unaltered at around 30 K. 28 This result poses another fundamental question, concerning why superconductivity should be so robust in the AFeSe system, and its answer requires a careful investigation into the effect of Tl, Rb, and Cs substitution on the microstructure of the FeSe layers in these materials.…”
mentioning
confidence: 99%